Ο ναός του Αγίου Γεωργίου στο Χουμνικό Σερρών - Σκιαδαρέσης, Γεώργιος Ν. (Μακεδονικά, 2011)
St George’s church in Chumnico a village in district of Serres belongsto the three-aisled basilica model, typical of the Turkish domination period,with a p-shapped narthex westwards. The three conches to the south of thesanctuary rank it among the double churches. The first structure of the churchdating back to 1753 as it is inscribed, was limited to today’s main part of thechurch in 1859, due to another inscription, the p-shapped narthex was addedin the west of initial structure. In the following decades up to 1875 the churchtook its present shape, after the main part of the church and the narthexslightly had been raised high, leading to a series of alterations to the exteriorand the interior church.